From the Piedmont to the Coast: LA‐ICP‐MS 87Sr/86Sr evidence for short‐term, long‐distance mobility in the American Southeast. (25th June 2020) - Quinn, R. L.; Prizzi, M.; Godfrey, L.; Setera, J. B.
Abstract : Mounting evidence suggests that the Archaic Southeast shell mound builders had large‐scale trade networks and engaged in social aggregations. Here, incremental 87 Sr/ 86 Sr values were measured by laser ablation‐inductively coupled plasma‐mass spectrometry (LA‐ICP‐MS) in third molar enamel samples of 11 individuals interred in the Middle Archaic Harris Creek shell burial mound in St. John's River Valley (SJRV), Florida. Results reveal that SJRV residents engaged in short‐term, long‐distance mobility up to the Piedmont margin and excursions into coastal areas, consistent with direct trading and social gatherings. Two individuals are interpreted as migrants from central Tennessee, suggesting a link to the Ohio River Valley shell mound builders.